IMPLEMENTASI SISTEM INFORMASI BERBASIS ANDROID UNTUK PROMOSI DAN PEMASARAN UMKM JAMUR TIRAM - Oktavia, Chaulina Alfianti; Dewantara, Risky (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are independent businesses owned by individuals or business entities. In Sumberjo Village, most residents are engaged in mushroom farming. The use of communication and information technology facilitates better access and convenience for the community and MSME actors in their marketing activities through electronic commerce (E-commerce). However, the MSMEs of Oyster Mushroom Farmers in Sumberjo Village face challenges with product marketing, as visitors often have difficulty locating the mushroom farms. This finding is based on interviews with several visitors. The village is known for producing a variety of mushrooms. The purpose of this Information System is to facilitate the media for information and promotion for MSMEs of Oyster Mushroom Farmers in Sumberjo Village, and to help market mushroom products, mushroom baglog seeds, and dried mushroom food preparations effectively and easily, both to the general public and online. This system also aids visitors in reaching the mushroom farms. The application was successfully developed using the native Java Android framework and CodeIgniter. It utilizes an API from Raja Ongkir for calculating shipping costs and includes Google Maps to assist visitors in finding the mushroom farms. This application successfully displays product information from the mushroom farmers, enabling them to use this application as a medium for information and promotion effectively.